Analysis of Tuna Fish Marketing Systems and Strategies - Amin, Muhtar; Asni, Asni; Nursalam, Nursalam (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2024)
Indonesia is a country that has great tuna potential. Indonesia is one of the tuna exporting countries on the world market. Kolaka is one of the districts that has a large catching capacity for tuna. Sales of tuna fish cannot be separated from relationships with marketing institutions, such as collecting traders, wholesalers and retailers, which are marketing institutions that connect producers and consumers. Research objectives are to determine the marketing channels for tuna fish, to determine the marketing margin of each marketing institution and tuna marketing channels, to determine the efficiency of tuna marketing, to determine the size of Farmer’s Share received by fishermen, and to find out the Tuna Fish marketing strategy in Kolaka Regency. The results of this research are that two marketing channels occur, of the two marketing channels, namely marketing channel I is less efficient with an efficiency value of 89.79% than marketing channel II with an efficiency value of 86.27%. The marketing margin in marketing pattern I obtains a relatively large total margin compared to the total margin in marketing pattern II. Farmer’s share obtained from each marketing channel is different. The tuna marketing strategy that can be used is development network market, promotion, product innovation as well as utilizing additional capital from the Government/Banks, improving the quality of human resources with training, using online media to promote new prices, making processed tuna fish.